Features of CAKUT syndrome (congenital anomalies of the kidney and urinary tract): clinical case - Sima F. Musoyan; Anastasia I. Solenova; Alexandra R. Mamedova; Marina A. Manina (LLC "MEDIAFORMAT", 2023)
A clinical observation of a child with a severe combined defect of the reproductive system and reproductive system (cAKuT syndrome) is presented. cAKuT syndrome accounts for more than 20% of birth defects. congenital anomalies of the urinary system account for 40-50% of cases of end-stage renal disease in children and 7% in adults worldwide. early diagnosis and treatment of cAKuT syndrome in children is one of the most important tasks of pediatric nephrology at present. It is necessary to monitor the course of the disease and assess the rate of development of unfavorable outcomes of chronic kidney disease. clinical observation of cAKuT syndrome is to optimize the therapeutic tactics of the underlying disease and reduce the disability of the child population.